2022
DOI: 10.1039/d2ra03376c
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the effects of nanoparticles on gas hydrate formation

Abstract: The use of nanoparticles and their effects on thermodynamics and kinetics during the hydrate formation process is summarized. For their application in drilling fluid and cement slurry, it is found nanoparticles must be used in conjunction with surfactants to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 88 publications
0
31
0
Order By: Relevance
“…Generally, systems with NPs exhibit a shorter induction time compared to pure water systems. 82,83,138 This observation indicates that the presence of NPs effectively reduces the time required for hydrate nucleation, leading to quicker initiation of the process. Numerous studies has revealed that the induction time reduces with rising NP concentrations.…”
Section: Nanoparticles-basedmentioning
confidence: 87%
“…Generally, systems with NPs exhibit a shorter induction time compared to pure water systems. 82,83,138 This observation indicates that the presence of NPs effectively reduces the time required for hydrate nucleation, leading to quicker initiation of the process. Numerous studies has revealed that the induction time reduces with rising NP concentrations.…”
Section: Nanoparticles-basedmentioning
confidence: 87%
“…17,18 In the case of gas hydrates, the nanoparticles ranging from 1 to 100 nm in size have been studied for their KHP-like behavior. 32 It was observed that studied nanoparticles effectively enhanced heat transfer and, to some extent, contributed toward mass transfer. 33 Silica nanoparticles were studied with diverse functionalizations imparting gas hydrate inhibition properties and are applicable in maintaining flow assurance.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of gas hydrates, the nanoparticles ranging from 1 to 100 nm in size have been studied for their KHP-like behavior . It was observed that studied nanoparticles effectively enhanced heat transfer and, to some extent, contributed toward mass transfer .…”
Section: Introductionmentioning
confidence: 99%
“…The gas hydrate as a CO 2 storage technology has experienced apparent acceleration among scientists, scholars and researchers at various levels as evident from the research publications analysis shown in Figure a. However, most of the research papers published in the CO 2 gas hydrate domain were focused on additives/nanoparticles, nucleation, kinetics, and their growth theories/models, and only a few were focused on oceanic sequestration, as shown in the Scopus data analysis (Figure a), especially in porous media that closely aligned with subsea basins. The majority of studies on the CO 2 sequestration in porous media were focused on the CO 2 –CH 4 exchange process not on subsea sedimentary CO 2 sequestration alone. , However, the in-depth analysis of hydrate-forming conditions in actual oceanic and subsea conditions in relation to NBZ and HFZ is not available in the open literature.…”
Section: Introductionmentioning
confidence: 99%